Analysis of Tunable Terahertz Generation in Gallium Phosphide Using Difference Frequency Mixing - Farooqui, Maria; Kumar, Vijay; Gupta, Arun Kumar (Journal of Graphic Era University, 2023)
<span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*351.65px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925546);" role="presentation">In this paper numerical analysis has been carried out to study the tunable terahertz (THz) generation in gallium <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*364.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.926494);" role="presentation">phosphide using difference frequency generation. By varying the input wavelengths in the range 930- <span dir="ltr" style="left: calc(var(–scale-factor)*487.66px); top: calc(var(–scale-factor)*364.85px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.925609);" role="presentation">1030 nm <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.946724);" role="presentation">we obtained 0.1-<span dir="ltr" style="left: calc(var(–scale-factor)*141.98px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(1.00088);" role="presentation">3 THz <span dir="ltr" style="left: calc(var(–scale-factor)*172.70px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.948704);" role="presentation">tunable THz f<span dir="ltr" style="left: calc(var(–scale-factor)*230.93px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.869741);" role="presentation">reque<span dir="ltr" style="left: calc(var(–scale-factor)*253.13px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922138);" role="presentation">ncy. <span dir="ltr" style="left: calc(var(–scale-factor)*273.17px); top: calc(var(–scale-factor)*378.05px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.95101);" role="presentation">Theoretical dependence of THz wave power on GaP crystal <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*391.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.91102);" role="presentation">length and <span dir="ltr" style="left: calc(var(–scale-factor)*117.62px); top: calc(var(–scale-factor)*391.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.928972);" role="presentation">effect of simultaneous tuning of both the input wavelengths has been studied. <span dir="ltr" style="left: calc(var(–scale-factor)*437.38px); top: calc(var(–scale-factor)*391.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907776);" role="presentation">The <span dir="ltr" style="left: calc(var(–scale-factor)*456.10px); top: calc(var(–scale-factor)*391.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.907217);" role="presentation">simulated <span dir="ltr" style="left: calc(var(–scale-factor)*498.10px); top: calc(var(–scale-factor)*391.25px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.884603);" role="presentation">values <span dir="ltr" style="left: calc(var(–scale-factor)*72.02px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.910285);" role="presentation">of THz peak power were 0.6 W, 0.7 W and 0.48 W which were obtained at 1.3, 2 and <span dir="ltr" style="left: calc(var(–scale-factor)*414.82px); top: calc(var(–scale-factor)*404.45px); font-size: calc(var(–scale-factor)*9.96px); font-family: sans-serif; transform: scaleX(0.922766);" role="presentation">2.7THz respectively.